Ferroptosis and Tumor Drug Resistance: Current Status and Major Challenges - Nie, Zhenyu; Chen, Mei; Gao, Yuanhui; Huang, Denggao; Cao, Hui; Peng, Yanling; Guo, Na; Wang, Fei; Zhang, Shufang (Frontiers in Pharmacology, 2022)
Ferroptosis is a novel type of regulated cell death, whose unique metabolic 19 characteristics are commonly used to evaluate the conditions of various diseases 20 especially in tumors. Accumulating evidence supports that ferroptosis can regulate 21 tumor development, metastasis, and therapeutic responses. Considering to the 22 important role of chemotherapy in tumor treatment, drug resistance has become the 23 most serious challenge. Revealing the molecular mechanism of ferroptosis is expected 24 to solve tumor drug resistance and find new therapies to treat cancers. In this review, 25 we discuss the relationship between ferroptosis and tumor drug resistance, summarize 26 the abnormal ferroptosis in tissues of different cancer types and current research 27 progress and challenges in overcoming treatment resistance, and explore the concept 28 of targeting ferroptosis to improve tumor treatment outcomes.